Cognitive impairment predicts social disability in persons with epilepsy - Bujarski Krzysztof A. (Journal of Epileptology, 2014)
Introduction. Cognitive dysfunction is one of the main comorbidities of epilepsy which co-exists with seizures and contributes to the adverse impact of the disease on employment, education and interpersonal relationships. A fundamental question regarding cognitive dysfunction in epilepsy goes as follows: in comparison to seizures, what role does cognitive dysfunction play in causing social disability? The purpose of this review was to evaluate our understanding of the role cognitive impairment plays in social disability in persons with epilepsy (PWE). We systematically searched the medical literature and identified studies which assessed the impact of seizures and cognitive function on some aspect of social disability in PWE.